A new herbal anesthetic agent for common carp (Cyprinus carpio) sedation and anesthesia: nutmeg (Myristica fragrans) essential oil - Minaz, Mert (Frontiers in Veterinary Science, 2024)
In aquaculture, interest in natural essential oils is increasing alongside synthetic anesthetic agents. In this context, the anesthetic efficacy of nutmeg essential oil, which had not been previously tested, was investigated in common carp (Cyprinus carpio). The study, conducted using three different concentrations (800 μL/L “LC”, 1,200 μL/L “MC”, and 1,400 μL/L “HC”), found that induction times were <3 min for MC and HC, while LC had a longer induction time, exceeding acceptable levels. Within the first 4 h, white blood cells, red blood cells, hemoglobin, and hematocrit levels increased to >5 103/μL, >1 106/μL, >6 g/dL, and >12%, respectively. However, they returned to control levels after 8 h. Histological signs were more severe with higher concentrations, and necrosis was only observed in the HC group. Alkaline comet assay results showed DNA migration only in the HC group. According to the PROMETHEE multi-criteria decision-making model, the LC concentration is suitable for sedation, while the MC concentration should be used for deep anesthesia. The current study demonstrates that nutmeg essential oil can be used as an alternative to commercial synthetic anesthetic agents.